Brazilian Paralympic sport initiation: The road from Rio to Los Angeles - Cardoso, V. D.; Haiachi, M. D. C.; dos Santos, A. C. A.; Canuto, S. C. M.; Nicoletti, L. P. (Journal of Human Sport & Exercise, 2020)
The Paralympic Games are the largest high-performance sport competition for athletes with disabilities (motor, visual and intellectual). Brazil is evolving in the medal table with each edition of the Games, and the country's growth and sporting improvement since the Sydney 2000 Paralympic Games. After Rio 2016 Paralympic Games grow up the necessity of renewal of Brazilian Paralympic talent. This study aims to bring reflections on the actions developed in Brazil that can contribute and improve the formation of new generations of Brazilian Paralympic athletes. This study are bibliographic search was conducted in national and international databases such as: SCIELO, Science Direct, Google Scholar, as well as in the Thesis Bank of the Coordination of Improvement of Higher Education Personnel (CAPES) and also in institutional documents and institutional websites. Paralympic School Games is the most recognized initiative of paralympic sports initiation and have already been the showcase of some of the most talented brazilian athletes and can be considered the main way to reveal new athletes with disabilities in Brazil. Also, University Paralympic Games, School Camping and Paralympic Training Center increase this process in Brazil. Thus, the Paralympic Games of 2024 and 2028, bring good perspectives for the brazilian paralympic sport, besides the possibility of proving the capacity of renewal of paralympic talents, can consolidate the continuity of the country as power in the world paralympic scenario.